2007
DOI: 10.1177/875512250702300207
|View full text |Cite
|
Sign up to set email alerts
|

Probable Elevation in International Normalized Ratio from Cranberry Juice

Abstract: WWW.JPHARMTECHNOL.COMSeveral health benefits of cranberries have been proposed, from urinary tract infection prophylaxis, possibly related to an anti-adhesion mechanism of bacteria in the bladder, to a cardioprotective effect by inhibiting lowdensity lipoprotein (LDL) oxidation and inducing LDL receptor expression. 1-3 The growing interest in alternative therapies, including phytonutrients, may lead to concomitant use of cranberry juice or products in patients receiving warfarin.Close monitoring of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The US Food and Drug Administration (FDA) agreed with MHRA/CSM and in 2006, advised manufactures of warfarin to update the package insert with the warning. The majority of evidence documenting the interaction is from case reports [86][87][88][89][90][91], however a study was published in 2006 investigating a possible mechanism for the interaction [92]. The authors suggested the cranberry flavonoid may alter the biosynthesis of CYP isoenzymes, especially CYP2C9, which would affect the metabolism of S-warfarin.…”
Section: Cranberry Juicementioning
confidence: 97%
“…The US Food and Drug Administration (FDA) agreed with MHRA/CSM and in 2006, advised manufactures of warfarin to update the package insert with the warning. The majority of evidence documenting the interaction is from case reports [86][87][88][89][90][91], however a study was published in 2006 investigating a possible mechanism for the interaction [92]. The authors suggested the cranberry flavonoid may alter the biosynthesis of CYP isoenzymes, especially CYP2C9, which would affect the metabolism of S-warfarin.…”
Section: Cranberry Juicementioning
confidence: 97%
“…96e99 Nonetheless, an interaction with warfarin cannot be ruled out, particularly when large volumes of cranberry juice are drunk regularly, or when cranberry products other than juice are taken. 96,97,100 Thus, the INR should be monitored more closely in patients on warfarin if they consume large amounts of cranberry juice or take other cranberry supplements for prophylaxis against UTIs. 96 Quantifying the effects of CYP450 inhibition and induction Quantification of the effects of CYP450 inhibitors and inducers is still evolving.…”
Section: Cyp450 Drugefood Interactionsmentioning
confidence: 99%
“…Interestingly, these clinical studies (21,25,27) used cranberry juice, unlike the Abdul et al (2008) study which used cranberry juice concentrate (26), raising speculation on the likely differences in the distribution of active principles between a cranberry concentrate vs juice. In this context, it is important to point out that several case reports have been published in the past several years that claim that ingestion of cranberry juice effects the INR and de-stabilizes the warfarin dose, necessitating a dose readjustment to obtain therapeutic anti-coagulant effect (38)(39)(40)(41)(42). In most of the instances, the acute consumption of cranberry juice was not deemed very high, with the exception of one or two instances where the patient drank almost 750 mL to 2 L of cranberry juice per day.…”
Section: Pharmacodynamicsmentioning
confidence: 99%